COVID-19 and Stock Return: Empirical Evidence from Developing Economy - Md. Rezaul Karim; Sifat Ara Saba (Zenodo, 2021)
This paper has tried to assess the impact of COVID-19 on stock return in different sectors listed under Dhaka Stock Exchange in Bangladesh during the period from 08 March 2020 to 15 September 2020. To measure the impact of COVID-19 on stock return, daily change in number of confirmed cases and deaths have been used as independent variables and DSE stock return has been taken as variable of interest. Data were collected from Bangladesh Government’s official portal, DSE archive and annual reports of listed firms. Sample is selected using two stage sampling method which is a probabilistic model. To test the validity of the used model, Pearson’s correlations analysis, Breusch and Pagan’s heteroscedasticity test, White’s homoscedasticity test and Hausman’s fixed random tests are conducted. After testing the validity, fixed effect method of panel data regression model has been used to test the two hypotheses. The result reveals that most of the sectors responded negatively to the growth in COVID-19 confirmed cases. It is also observed that selected sectors reacted more proactively to the growth in number of deaths as compared to the growth in number of confirmed cases. Where banking and textile sectors are the most sufferers to the growth of both confirmed cases and deaths, pharmaceuticals & chemicals industry proved out to be the gainers. The findings will have policy implications for the regulators as well as for the investors to design the optimum portfolio of investment. The study will add new dimensions to the existing literature. : {"references": ["Ahmed, S. Y. (2020). Impact of COVID-19 on Performance of Pakistan Stock Exchange. Munich Personal RePEc Archive.", "Al-Awadhi, A.M., Al-Saifi, K., Al-Awadhi, A. and Alhamadi, S. (2020). Death and Contagious Infectious Diseases: Impact of the COVID-19 Virus on Stock Market Returns. Journal of Behavioral and Experimental Finance, 27, 100-326. Available through: doi:10.1016/j.jbef.2020.100326.", "Alfaro, L., Chari, A., Greenland, A. N. and Schott, P. K. (2020). Aggregate and Firm-Level Stock Returns During Pandemics, in Real-Time. National Bureau of Economic Research.", "Ali, N., Nassir, A., Hassan, T., and Abidin, S. (2010). Short Run Stock Overreaction: Evidence from Bursa Malaysia. International Journal of Economics and Management, 4, 319-333.", "Ashraf, B.N. (2020). Stock Markets' Reaction to COVID-19: Cases or Fatalities? Research in International Business and Finance, 54, 101-249, doi: 10.1016/j.ribaf.2020.101249.", "Baker, C.R., Bloom, N., Davis, S.J., Kost, K., Sammon, M. and Viratyosin, T. (2020). The Unprecedented Stock Market Reaction to COVID-19. NBER Working Paper No. 26945. [Online] Available at: https://bfi.uchicago.edu/wp-content/uploads/BFI_WhitePaper_Davis_3.2020.pdf [Accessed 07 October 2020]", "Becchetti, L. and Ciciretti, R. (2011). Stock Market Reaction to the Global Financial Crisis: Testing For the Lehman Brothers' Event. Giornale degli Economisti e Annali di Economia, 3-58.", "Chen, C.D., Chen, C.C., Tang, W.W. and Huang, B.Y. (2009). The Positive and Negative Impacts of the SARS Outbreak: A Case of the Taiwan Industries. The Journal of Developing Areas, 43(1), 281-293. [Online]. Available at: https://www.jstor.org/stable/40376284 [Accessed 07 October 2020]", "Chen, M.H., Jang, S., and Kim, W. (2007). The Impact of the SARS Outbreak on Taiwanese Hotel Stock Performance: An Event-Study Approach. International Journal of Hospitality Management, 200-212.", "Chou, J., Kuo, N.F., and Peng, S.L. (2004). Potential Impacts of the SARS Outbreak on Taiwan's Economy. Asian Economic Papers, 3, 84-99.", "Dewatripont, M., Goldman, M., Muraille, E. and Platteau, J.P. (2020). Rapidly Identifying Workers Who Are Immune to Covid-19 and Virus-Free Is a Priority for Restarting the Economy. Available at: VoxEU.org [Accessed 07 October 2020]", "Ding, W., Levine, R., Lin, C. and Xie, W. (2020). Corporate Immunity to the COVID-19 Pandemic. National Bureau of Economic Research.", "Gan, C. and Le Trang, D. (2020). The Impact of the COVID-19 Lockdown on Stock Market Performance: Evidence from Vietnam. Journal of Economic Studies. DOI 10.1108/JES-06-2020- 0312", "Gangopadhyay, P., Haley, J.D. and Zhang, L. (2010). An Examination of Share Price Behavior Surrounding the 2005 Hurricanes Katrina and Rita. Journal of Insurance Issues, 132-151", "Ghasemi, A. and Zahediasl, S. (2012). Normality Tests for Statistical Analysis: A Guide for NonStatisticians. International Journal of Endocrinology and Metabolism. [Online]. Available at: http://dx.doi.org/10.5812/ijem.3505[Accessed 08 October 2020].", "Goodell, J.W. (2020).COVID-19 and Finance: Agendas for Future Research. Finance Research Letters.35, 101-512. Available through: doi: 10.1016/j.frl.2020.101512.", "Hair, J. F. Jr., Money, A. H., Samouel, P. and Page, M. (2007).Research Methods for Business. England: John Wiley & Sons. [Online]. Available at: https://digitalcommons.kennesaw.edu/ facpubs/2952/ [Accessed 10 October 2020].", "Hair, J., Black, B., Babin, B., Anderson, R., & Tatham, R. (2006). Multivariate Data Analysis. 7th edn. Harlow: Pearson Education. [Online]. Available at: https: //is.muni.cz/el/1423/podzim2017/PSY028/um/_Hair_Multivariate_data_ analysis_7th _revised. Pdf [Accessed 29 January 2019].", "He, Q., Liu, J., Wang, S. and Yu, J. (2020). The Impact of COVID-19 on Stock Markets\",", "Economic and Political Studies, 8 (3), 1-14. Available through: doi: 10.1080/ 20954816.2020.1757570.", "Jiang, Y., Zhang, Y., Ma, C., Wang, Q., Xu, C., Donovan, C. and Sun, W. (2017).H7N9 Not Only Endanger Human Health but Also Hit Stock Marketing. Advances in Disease Control and Prevention, 2(1), 1-7. Available through: doi: 10.25196/adcp201711.", "Kent, J.A. (2007). Kent and Riegel's Handbook of Industrial Chemistry and Biotechnology. [Online]. Available at: https://www.scribd.com/document/3609705 42/Kent-and-Riegel-sHandbook-of-Industrial-Chemistry-and-Biotechnology-11va-Ed [Accessed 01 October 2020].", "Kodres, L. (2020). Brakes or Bans: Protecting Financial Markets during a Pandemic. [Online] Available at: https://voxeu.org/article/brakes-or-bans-protecting-financial-markets-during- pandemic [Accessed 27 September 2020].", "Kotishwar A. (2020). Impact of Covid-19 Pandemic on Stock Market with Reference to Select Countries \u2013 A Study. Academy of Accounting and Financial Studies Journal, 24(4)", "Kowalewski, O. and \u015apiewanowski, P. (2020). Stock Market Response to Potash Mine Disasters. Journal of Commodity Markets.", "Lee, J.W., and McKibbin W. (2004). Globalization and disease: The case of SARS. Asian Economic Papers.", "Liu, H., Manzoor, A., Wang, C., Zhang, L. and Manzoor, Z. (2020). The COVID-19 outbreak and affected countries stock markets response. International Journal of Environmental Research and Public Health, 17(8), 2800. Available through: doi: 10.3390/ijerph17082800.", "Nippani, S. and Washer, K.M. (2004). SARS: A Non-Event for Affected Countries' Stock Markets? Applied Financial Economics, 14 (15), 1105-1110. Available through: doi: 10.1080/096031004 2000310579.", "Schoenfeld, J. (2020). The Invisible Risk: Pandemics and the Financial Markets. Available at: SSRN 3567249[Accessed 27 September 2020].", "Siu, A. and Wong, R. (2004). Economic Impact of SARS: The Case of Hong Kong. Asian Economic Papers, 3, 62-83", "Topcu, M. and Gulal, O. S. (2020). The impact of COVID-19 on emerging stock markets. Finance Research Letters. Available at: www.elsevier.com/locate/frl [Accessed 27 September 2020].", "Williams, C. (2007). Research Methods. Journal of Business & Economic Research. [Online]. Available at: https://doi.org/10.19030/jber.v5i3.2532 [Accessed 08 October 2020].", "Zhang, D., Hu, M. and Ji, Q. (2020). Financial markets under the global pandemic of COVID19.Finance Research Letters. Available at: https://doi.org/10.1016/j.frl. 2020.101528 [Accessed 27 September 2020].", "Zhang, D., Hu, M. and Ji, Q. (2020).Financial markets under the global pandemic of COVID-19.", "Finance Research Letters. In press, p. 101528, Available through: doi:10.1016/j.frl.2020. 101528.", "Zikmund, W. (2003).Business Research Methods. 7th edn. USA: Thomson South Western."]}